Steamship Service to Alaska (1898) - North American Transportation and Trading Company (1898)
Klondike: a commodious and fast sailing steamer will leave Seattle on or about June 10, 1898. And every ten days thereafter, taking freight and passengers, for Fort Get There, St. Michael's Island, Alaska, mouth of the Yukon River, making connections with the river steamers.Placer and quartz mines bought and sold. Investments in mining property made, saving expense of sending agents. We will issue letters of credit on our company at its posts.at a charge of 1 percent. In the 1890s, the North American Transportation and Trading Company of Chicago, Illinois established stations and operated mines throughout Alaska and the Yukon Territory. Klondike Gold Rush Steamships, ferries and boats Transportation and communication Real estate and land development